Measles, mumps, rubella prevention: how can we do better?. (3rd July 2021) - Kauffmann, Florence; Heffernan, Catherine; Meurice, François; Ota, Martin O. C.; Vetter, Volker; Casabona, Giacomo
ABSTRACT: Introduction: Measles, mumps, and rubella incidence decreased drastically following vaccination programs' implementation. However, measles and mumps' resurgence was recently reported, outbreaks still occur, and challenges remain to control these diseases. Areas covered: This qualitative narrative review provides an objective appraisal of the literature regarding current challenges in controlling measles, mumps, rubella infections, and interventions to address them. Expert opinion: While vaccines against measles, mumps, and rubella (including trivalent vaccines) are widely used and effective, challenges to control these diseases are mainly related to insufficient immunization coverage and changing vaccination needs owing to new global environment (e.g. traveling, migration, population density). By understanding disease transmission peculiarities by setting, initiatives are needed to optimize vaccination policies and increase vaccination coverage, which was further negatively impacted by COVID-19 pandemic. Also, awareness of the potential severity of infections and the role of vaccines should increase. Reminder systems, vaccination of disadvantaged, high-risk and difficult-to-reach populations, accessibility of vaccination, healthcare infrastructure, and vaccination services management should improve. Outbreak preparedness should be strengthened, including implementation of high-quality surveillance systems to monitor epidemiology. While the main focus should be on these public health initiatives to increase vaccination coverage, slightly more benefits could come from evolution of current vaccines. PLAIN LANGUAGE SUMMARY: What is the context? Measles, mumps, and rubella are highly contagious diseases associated with significant medical and societal burden. Effective vaccines against these diseases are available, and the implementation of vaccination programs drastically reduced disease incidence globally. However, reports of measles and mumps outbreaks in the last few years highlight remaining challenges to eliminate these diseases. What does the review highlight? We conducted a literature review to identify challenges associated with controlling measles, mumps, and rubella infections, and interventions needed to address them. We identified 11 challenges mainly related to low immunization coverage and vaccine characteristics. Societal challenges could be addressed by increasing awareness of disease severity and vaccines impact, targeting high-risk, unvaccinated, and under-vaccinated populations, improving vaccination access, setting up clear outbreak preparedness plans, and implementing country-specific vaccination policies. System weaknesses could be addressed through improving vaccination services and health infrastructure, implementing high-quality surveillance, patient invite, and reminder systems, ensuring vaccine implementation and long-term supply. Interventions related to vaccine characteristic challenges could include adaptation of vaccination schedules (shorter interval between doses, administration of a third dose) and development of vaccines against emerging strains. What is the take-home message? Policymakers should support the following strategies to increase vaccination coverage and reach elimination of measles, mumps, and rubella: strengthening health systems and vaccination access; raising awareness of disease severity and vaccination impact; limiting disease propagation owing to global changing environment and population dynamics (traveling, migration); improving surveillance systems to rapidly address the immunity gaps against disease resurgence.